Current Update of Pharmacogenomic in Drug Discovery and Development : A narrative review - Istifarwati; Isvina Unai Zahroya; Marga Putri, Elvia Rahmi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Pharmacogenomics currently has an essential role in drug discovery and development. Research related to pharmacogenomics has increased rapidly since the human genome project was completed in the early 20th century, increasing awareness of the importance of personalized medicine, which is expected to be safer and more beneficial for human health. Therefore, this article aims to review recent developments regarding pharmacogenomics in drug discovery and development. In addition, this article will also discuss the challenges that still exist in the implementation of pharmacogenomics in drug development and clinical practice. It is hoped that these challenges can be overcome in the future with collaboration between researchers, practitioners, and the government so that precision and personalized therapy can be realized for each individual. Keywords: drug discovery, drug development, pharmacogenetic, pharmacogenomic